THE FORMATION OF HARD SPRING WHEAT YIELD DEPENDING ON MINERAL FERTILIZERS AND MICROBIOLOGICAL PREPARATIONS IN THE CONDITIONS OF LEFT-BANK FOREST-STEPPE - Shevnikov, D.M. (Scientific Progress & Innovations, 2019)
In the conditions of unstable and insufficient moistening, it is necessary to study basic technological ele-ments of hard spring wheat cultivation in the context of climate change. Complex study and analysis were conducted concerning the using of microbiological preparations depending on the background of mineral fertilizing in the technologies of hard spring wheat cultivation. The formation of plant leaf surface depended on both the background of mineral fertilizing and using microbiological preparations. On plots without ferti-lizing, seed treatment with bio-preparations resulted in increasing leaf area by 20.3 % after using polymixo-bacterin, 20.5 % after diazophyte, and 23.9 % when using a mixture of these two biologics. It amounted to 31.9 thousand m2/ha after fertilizing with N45P45K30, applying polymixobacterin led to leaf area increase by 19.1 %, diazophyte – by 13.8 %, and the mixture of biologics – by 24.1 %. Straw + N10 fertilization back-ground per ton of by-product was effective, as the leaf area was quite large (29.2 thousand m2/ha) and 33.9; 32.9; 36.4 thousand m2/ha, respectively, while using biologics. The yield of hard spring wheat is determined by the number of productive stems per area unit and grain weight per ear. They were the largest on the plots sowed with seeds inoculated with polymixobacterin and diazophyte against the background of N45P45K30 fer-tilizing – 3.50 t/ha, which was 1.47 t/ha (72.4 %) more than on plots without using mineral fertilizers and biologics (2.03 t/ha). The rational way to increase the yield of hard spring wheat is to apply straw + N10 fer-tilizer per ton of by-product with compulsory pre-sowing seed treatment with a mixture of biologics. In such case the grain yield was 3.16 t/ha, that is, 1.13 t/ha (55.7 %) more than while cultivating without fertilizers. In the conditions of unstable moistening in the technology of hard spring wheat cultivation, it is necessary to apply seed pre-sowing treatment with diazophyte and polymixobacterin biologics against the background of straw as precursor, after its harvesting and obligatory N10 application per each ton of by-products, which will ensure wheat grain yield 3.16 t/ha. In case of the absence of precursor by-products, it is necessary to conduct seed pre-sowing treatment with diazophyte and polymixobacterin biologics and obligatory applying N45P45K30, which will ensure wheat grain yield at the level of 3.50 t/ha. In the future, it is necessary to carry out the study of introducing new microbiological biologics depending on the background of mineral fertiliz-ing in spring wheat cultivation technologies, to determine directions and prospects of scientific research and practical application in production.